Kepler observations of three pre-launch exoplanet candidates: discovery of two eclipsing binaries and a new exoplanet - Howell, Steve Bruce; Rowe, Jason F.; Sherry, William; von Braun, Kaspar; Ciardi, David R.; Bryson, Stephen T.; Feldmeier, John J.; Horch, Elliott P.; van Belle, Gerard T. (The Astrophysical Journal, 2010)
Three transiting exoplanet candidate stars were discovered in a ground-based photometric survey prior to the launch of NASA's Kepler mission. Kepler observations of them were obtained during Quarter 1 of the Kepler mission. All three stars are faint by radial velocity follow-up standards, so we have examined these candidates with regard to eliminating false positives and providing high confidence exoplanet selection.We present a first attempt to exclude false positives for this set of faint stars without high-resolution radial velocity analysis. This method of exoplanet confirmation will form a large part of the Kepler mission follow-up for Jupiter-sized exoplanet candidates orbiting faint stars. Using the Kepler light curves and pixel data, as well as medium-resolution reconnaissance spectroscopy and speckle imaging, we find that two of our candidates are binary stars. One consists of a late-F star with an early M companion, while the other is a K0 star plus a late M-dwarf/brown dwarf in a 19 day elliptical orbit. The third candidate (BOKS-1) is an r = 15 G8V star hosting a newly discovered exoplanet with a radius of 1.12 RJupiter in a 3.9 day orbit. © 2010 The American Astronomical Society. All rights reserved.
Keywords: Binaries: eclipsing; Brown dwarfs; Planetary systems; dept.phy